Bibliometric Analysis of Road Performance and Level of Service (LoS) Using VOSviewer - Indra Permana; Adhitya Akta Permana; Anisa Awaliyah; Asep Dian Herdiyana; Joewono Prasetijo (Fakultas Teknik Sipil dan Perencanaan, 2025)
This study aims to identify research trends, dominant themes, and keyword linkages in the scientific literature on road performance and level of service (LoS) using a bibliometric approach. Bibliographic data were collected from 1,000 publications using Publish or Perish and analyzed using VOSviewer software. The visualization results showed that the keywords